Urban Memory and Visual Culture in Berlin Framing the Asynchronous City, 1957-2012 - Ward, Simon (Cities and Cultures, 2016)
As sites of turbulence and transformation, cities are machines for forgetting. And yet archiving and exhibiting the presence of the past remains a key cultural, political and economic activity in many urban environments. This book takes the example of Berlin over the past four decades to chart how the memory culture of the city has responded to the challenges and transformations thrown up by the changing political, social and economic organization of the built environment. The book focuses on the visual culture of the city (architecture, memorials, photography and film). It argues that the recovery of the experience of time is central to the practices of an emergent memory culture in a contemporary 'overexposed' city, whose spatial and temporal boundaries have long since disintegrated.